Hypersurface Observation Network (Hyperon): what it is and why we need it - Erickson, Adam; Kumar, Sujay V.; Hudson, Derek l; Stamnes, Snorre; Puttonen, Eetu; Junttila, Samuli; Pirk, Sören; Höfle, Bernhard; Chrostowski, Lukas; Eitel, Jan; Calders, Kim (AGU Fall Meeting 2021, 2021)
In the terrestrial domain, large biogeochemical and energetic uncertainties sur...
Gesehen am 18.04.2024